FROM DIVERSITY TO INCLUSION: IMPACTS ON ORGANIZATIONAL BEHAVIOR - Jorovlea, Elvira; Baieșu, Marina (SWorld-Ger Conference proceedings, 2025)
Diversity management in organizations involves the strategic implementation of policies and practices aimed at creating an inclusive, equitable, and respectful workplace environment for all employees, regardless of their backgrounds. Its evolution has shi